INFRASTRUCTURE DESIGN OF RESTRICTED SECURITY AREA FENCING TO ENHANCE AIRPORT SECURITY - Ahmad Ardi Zulkarnain; Achmad Muhyidin Arifai; Deni Priansyah (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to develop a technically compliant and economically feasible design for a Restricted Security Area (RSA) perimeter fence surrounding Substation 7, the Chiller facility, and the Ground Water Tank (GWT) at Kertajati International Airport. These facilities constitute critical operational infrastructure supporting electricity distribution, terminal cooling systems, and water supply, including fire suppression reserves. Field observations identified the absence of a regulation-compliant perimeter protection system, exposing the utility cluster to unauthorized access and operational risk. The research employed a quantitative descriptive–analytical approach integrating field measurement, engineering design modeling, volume computation, and cost estimation based on the 2024 Majalengka Regional Standard Unit Price. Technical evaluation referred to national aviation security regulations and ICAO Annex 17 principles. A BRC (British Reinforced Concrete) fence system with a total height of 3.20 meters (2.40 m fence body and 0.80 m concertina wire) was proposed. The structural configuration includes reinforced concrete isolated footings, tie beams (sloof), and a bottom plinth beam to ensure lateral stability and anti-climb resistance. The total perimeter length of 313.74 meters ensures complete enclosure of the critical facilities. The estimated total project cost amounts to IDR 509,553,000.00, including VAT. The results demonstrate that the proposed design is structurally reliable, regulation-compliant, and economically justified within a risk mitigation framework. The study contributes a replicable engineering and financial planning model for strengthening airport critical infrastructure protection and enhancing long-term operational resilience.